Karakteristik fisiko-kimia dan sensori mayones dari minyak sawit merah dengan penambahan ekstrak jahe var. Rubrum [Characteristic physicochemical and sensory red palm oil mayonnaise addition extract ginger var. Rubrum] - Farida Hanum Hamzah; Dewi Fortuna Ayu; Evy Rossi; Yossie Kharisma Dewi; Arya Dika (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2023)
Mayonnaise is an oil in water (O/W) emulsion despite containing 70–80% fat and egg yolk. The addition of extract ginger var. Rubrum serves as an ingredient that is able to cover the characteristic of mayonnaise of red palm oil taste and aroma and also contains high antioxidants. The aim was to find the best mayonnaise of red palm oil with extract ginger var. Rubrum addition according to the SNI. The experimental was arranged in a completely randomized design (CRD) with 3 treatments and replicated 3 times then continued tested using DNMRT at a 5% level. The treatment was five-level extract ginger var. Rubrum addition: 0.5%, 1%, 1.5%, 2%, and 2.5%. Parameters observed were moisture content, antioxidant activity, color with a colorimeter, and sensory evaluation on mayonnaise. The result showed that the addition of extract ginger var. Rubrum significantly affected color, descriptive sensory assessments such as aroma, taste, and viscosity, hedonic assessments such as aroma and taste. Whereas moisture content, color sensory assessment and hedonic viscosity were not significantly affected. The best treatment was 2.5% addition of extract ginger var. Rubrum with a value of 25.83% moisture content, 87.45 ppm (strong) antioxidant activity, color with colorimeter L*: 55.27; a*: 11.36; and b*: 48.86 and preferred overall acceptance.